Current status and future prospects for biologic treatments of psoriasis. (1st December 2016) - Cline, Abigail; Hill, Dane; Lewallen, Robin; Feldman, Steven R.
ABSTRACT: Introduction : Biological agents have transformed psoriasis treatment by selectively targeting immune signaling molecules involved in psoriasis pathogenesis. While biologics offer the most effective treatment of moderate to severe psoriasis, they are not without complications. Some patients treated with biologics have poor clinical responses, form anti-drug antibodies, or develop adverse events. Additionally, there is growing need for head-to-head studies comparing biologic treatment regimens, efficacy, and safety. Areas covered : Here we review the literature surrounding biologics already in clinical use and those undergoing development and clinical trials. We also investigate the development and approval of small molecules inhibitors and biosimilars used to treat psoriasis. Expert commentary : As the psoriasis treatment armamentarium continues to expand, it is important to follow the safety profile of these drugs both in clinical trials and in post-marketing registries to ensure their long-term safety. Physicians must be aware of the limitations of existing safety data of a drug and the potential risk for rare adverse events when selecting appropriate treatments and monitoring patient outcomes.